PENGGUNAAN ALAT PERAGA DAKOTA DALAM PEMBELAJARAN MATEMATIKA OLEH MAHASISWA PGSD UNIVERSITAS QUALITY BERASTAGI - Ratna Wahyuni; Novi Tari Simbolon; Deby Julianda Reulina Sitepu (MES: Journal of Mathematics Education and Science, 2023)
Abstract. The purpose of this study was to determine the level of understanding of Elementary School Teacher Education Students as prospective teachers regarding the use of Dakota visual aids in learning mathematics. This research was conducted in the Elementary School Teacher Education Study Program, University of Quality, Berastagi, with a population and sample of 28 students in Semester 1 of the 2022/2023 Academic Year. The type of research used is classroom action research. Based on the research conducted, PGSD students have various levels of understanding about the use of the Dakota visual aid in teaching the smallest common multiple and the largest common factor. The difference in the level of understanding is caused by differences in students' cognitive abilities. The evaluation results show that the percentage of students' understanding of the five material components assessed is as follows: regarding the teaching of multiples material, 53.57% of students have an understanding in the high category and 46.43% in the medium category. For teaching factors there are 50% of students with understanding in the high category and the other 50% are in the medium category. For fellowship teaching there are 57.14% of students with understanding in the high category. 28.57% of students are in the medium category and 14.29% of students with low understanding. For KPK teaching, there were 89.29% of students with an understanding in the high category and another 10.71% in the medium category. For FPB teaching, there are 71.43% of students with an understanding in the high category, 17.86% of students with moderate understanding, and another 10.71% with a low category.